Organizational factors influencing recreational therapy program effectiveness in veterans’ nursing homes: A mixed-methods approach - Mohammad Najeh Samara; Kimberly D. Harry; Brittany Weissman; Kara V. Dopp (PLoS ONE, 2026)
Background Veterans’ nursing homes face significant challenges in delivering effective recreational therapy (RT) programs due to complex organizational factors and unique veteran care needs. Limited research has systematically examined organizational determinants from leadership perspectives, despite leaders’ critical roles in resource allocation and program implementation. Objective This study examined organizational factors influencing recreational therapy program effectiveness in a veterans’ nursing home through comprehensive analysis of leadership perspectives using a mixed-methods approach. Methods A cross-sectional survey was administered to 19 leadership personnel at NYSVETS Home @ Oxford. The 28-question survey assessed RT program effectiveness across five well-being domains, organizational strengths and weaknesses, participation barriers, and leadership involvement patterns. Analysis included descriptive statistics, correlation analysis, and systematic thematic coding of 192 qualitative responses. Results Leadership rated overall RT program effectiveness highly (78.9%, 95% CI: 60.6–97.3%), with Physical well-being showing the highest impact (3.75 ± 0.62, 95% CI: 3.36–4.14) and no significant differences across domains (χ² = 0.563, p = 0.967, Kendall’s W = 0.007). Organizational strengths significantly outweighed weaknesses (U = 24.0, p = 0.010, effect size r = 0.741), with activity variety (89.5%) as the primary asset and resource limitations (52.6%) as the key deficit. Strong positive correlations emerged between engaged veterans and dedicated staff (r = 0.782, 95% CI: [0.508, 0.912]). Leadership demonstrated strong mission-vision alignment (76.5%) but involvement intensity showed no significant association with effectiveness (r = 0.335, 95% CI: [−0.214, 0.723], p = 0.223). A Resource Adequacy Index of 29.7% indicated critical capacity limitations. Qualitative analysis validated quantitative findings, with Social Interaction (40 mentions) and Physical Health (36 mentions) themes supporting effectiveness priorities while revealing veteran-specific challenges including generational preferences for individualized programming. Conclusions This study provides comprehensive evidence for organizational factors influencing RT effectiveness, demonstrating both program strengths and critical improvement areas. The organizational priority matrix and resource allocation analysis provide evidence-based tools for strategic planning and quality improvement initiatives, informing policy development and practical guidance for healthcare administrators.